Ozone sensing properties of nickel phthalocyanine:ZnO nanorod heterostructures - Joshi, Nirav [UNESP]; Shimizu, Flavio M. [UNESP]; Awan, Iram T. [UNESP]; M'Peko, Jean-Claude [UNESP]; Mastelaro, Valmor R. [UNESP]; Oliveira, Osvaldo N. [UNESP]; Silva, Luis F. da [UNESP]; IEEE (Ieee, 2016)
We report on the chemiresistive gas sensing characteristics of ZnO nanorods (NRs) modified by a thin layer of nickel phthalocyanine (NiPc). Ozone detection was carried out through electrical measurements with an optimized performance at 250 degrees C, good reproducibility and suitable concentration range (from 80 to 890 ppb) for technological applications. The hybrid NiPc: ZnO films had superior performance to pure ZnO nanorods in terms of response time and sensitivity. The response times were 22 s and 26 s, respectively, whereas the ratio of resistances under ozone and air was 3.27 for NiPc: ZnO films and 2.56 for the pure ZnO NRs. The improvement in response time is attributed to the large surface area generated with the coating of the ZnO nanorods with the NiPc layer. Significantly, images taken with field-emission scanning electron microscopy (FE-SEM) indicated that the ZnO nanorods were fully covered with NiPc. X-ray diffraction measurements (XRD) revealed a preferential growth of the nanorod-like structures along the [100] direction. In summary, a successful approach has been developed to functionalize ZnO nanorods, which is promising for detection of ppb levels of ozone gas.
Keywords: Hydrothermal technique; heterostructures; Ozone; Gas sensing